2008
DOI: 10.1007/s00223-008-9138-1
|View full text |Cite
|
Sign up to set email alerts
|

Osteoadherin is Upregulated by Mature Osteoblasts and Enhances Their In Vitro Differentiation and Mineralization

Abstract: During the process of differentiation, osteoblasts commit through strictly controlled checkpoints under the influence of several growth factors, cytokines, and extracellular matrix (ECM) proteins. The mineralized tissue-specific ECM component osteoadherin (OSAD) belongs to the small leucine-rich repeat protein family of proteoglycans. Proteoglycans modulate cellular behavior either through the attached glycosaminoglycan chains or by direct protein-protein interactions via the core protein sequences. Leucine-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 215 publications
(182 reference statements)
4
25
0
3
Order By: Relevance
“…Increasing TNAP activity is a prerequisite for increasing phosphate amounts at the site of mineralization and lead in consequence to increasing calcium phosphate deposition. Osteoadherin (¼osteomodulin, OSAD) is an extracellular matrix keratan sulfate-containing proteoglycan which is involved in a controlling mineralization process in bones and teeth [45]. Other typical osteogenic markers as collagen typ 1, osterix, and osteocalcin are suppressed by dex [41,43].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing TNAP activity is a prerequisite for increasing phosphate amounts at the site of mineralization and lead in consequence to increasing calcium phosphate deposition. Osteoadherin (¼osteomodulin, OSAD) is an extracellular matrix keratan sulfate-containing proteoglycan which is involved in a controlling mineralization process in bones and teeth [45]. Other typical osteogenic markers as collagen typ 1, osterix, and osteocalcin are suppressed by dex [41,43].…”
Section: Discussionmentioning
confidence: 99%
“…2C) which belong to the small leucine rich repeat family (SLRP) show increased expression in osteoblasts during differentiation [21,22]. Recent published studies show 1) that when 2T3 cells (preosteoblast cells) become confluent in culture, they increase expression of Osterix , DLX5, BMP2 and Osteomodulin [23] and 2) over expression of Osteomodulin in vitro leads to increased osteoblast differentiation [24]. We also observed that Runx2 the major osteoblast transcriptional factor and its target gene Osteocalcin are upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…expressions were induced 18) . Interestingly, OMD gene overexpression in MC3T3-E1 cells resulted in an increase of osteoblastic differentiation features, such as increased alkaline phosphatase activity and increased in vitro mineralization 19) .…”
Section: Discussionmentioning
confidence: 99%